Violência velada e revelada contra idosos em Minas Gerais: análise de denúncias e notificações realizadas nos anos 2011-2012 - Regina da Cunha Rocha (2014)
The aim of this dissertation was to identify and publicize the situation of violence against elder, informed from complaints and notifications made in the state of Minas Gerais. The results are presented in two articles. The first aims to identify literature on aspects that influence the notifications and complaints of violence against the elderly, contributing to the improvement of surveillance and the unveiling of the magnitude of the condition. In this is performed a review of scientific articles, supplemented by laws, books and technical books, published between 2003 and 2013. Articles were selected according to four categories is taken: violence (33%); information (27%); public policies (20%); social perception (20%), in which they discuss the concepts, typologies and factors associated with violence; the information; the need for ownership and democratic construction of relevant legislation and social perception. Emerged from the analysis issues that could increase complaints or notifications including change to the Statute of the Elderly, the potentiation of Dial 100 and mandatory notifications, building positive images of old age. Among the issues that contribute tothe reduction of communication are the rejection of old age, fragile Policy for the Elderly, age homogeneity, multiplicity of data sources and lack of support networks. The second article seeks to characterize the violence against elderly in Minas Gerais,from complaints and notifications recorded in Dial Information and Human Disease Notification System in 2011 and 2012 rights. It was recorded in the period 2.337 (12.7%) and complaints 1.886 (5.8%) notifications against the elderly. The complaint rate increased from 26 to 70 per hundred thousand elderly people, an increase of 2.7 times. About 70% of complaints are women, battered at home (90%) by known (90%), predominantly (80%) of the typology for negligence / abandonment, followed by psychological / moral and financial / economic. The notification rate increased from 25 to 52 per hundred thousand elderly people, an increase of 2.1 times in a year. Notifications in 57% of victims are women victimized in residence (85%), the children (31%). There was a predominance of physical, psychological, self-provoked and neglect violence, which together account for 88% of notifications. The logistic model showed how physical violence associated with independent factors: the victim being male (OR = 1.81 CI 95% 1.25 -2.69), being 60-69 years old (OR = 2.28 95% 1.45 -3.61) or 70-79 years old (OR = 1.68 CI 95% 1.03 -2.74), the use of alcohol by the perpetrator (OR = 2.05 CI 95% 1.42 -2.97) and being away from home. It is expected that led to the strengthening and improvement of surveillance studies, contribute to reveal violence against elderly in all its guises and enable implementation of effective public policies and action of the whole society.